Genome-Wide Characterization and Expression Analysis of the HD-ZIP Gene Family in Response to Salt Stress in Pepper - Zhongrong Zhang; Ranran Zhu; Xuehua Ji; Hui Ji Li; Hui Lv; Hai Ying Zhang (International Journal of Genomics)
HD-ZIP is a unique type of transcription factor in plants, which are closely linked to the regulation of plant growth and development, the response to abiotic stress, and disease resistance. However, there is little known about the HD-ZIP gene family of pepper. In this study, 40 HD-ZIP family members were analyzed in the pepper genome. The analysis indicated that the introns number of Ca-HD-ZIP varied from 1 to 17; the number of amino acids was between 119 and 841; the theoretical isoelectric point was between 4.54 and 9.85; the molecular weight was between 14.04 and 92.56; most of them were unstable proteins. The phylogenetic tree divided CaHD-ZIP into 4 subfamilies; 40 CaHD-ZIP genes were located on different chromosomes, and all of them contained the motif 1; two pairs of CaHD-ZIP parallel genes of six paralogism genes were fragment duplications which occurred in 58.28~88.24 million years ago. There were multiple pressure-related action elements upstream of the start codon of the HD-Z-IP family. Protein interaction network proved to be coexpression phenomenon between ATML1 (CaH-DZ22, CaHDZ32) and At4g048909 (CaHDZ12, CaHDZ31), and three regions of them were highly homology. The expression level of CaHD-ZIP gene was different with tissues and developmental stages, which suggested that CaHD-ZIP may be involved in biological functions during pepper progress. In addition, Pepper HD-ZIP I and II genes played a major role in salt stress. CaHDZ03, CaHDZ 10, CaHDZ17, CaHDZ25, CaHDZ34, and CaHDZ35 were significantly induced in response to salt stress. Notably, the expression of CaHDZ07, CaHDZ17, CaHDZ26, and CaHDZ30, homologs of Arabidopsis AtHB12 and AtHB7 genes, was significantly upregulated by salt stresses. CaHDZ03 possesses two closely linked ABA action elements, and its expression level increased significantly at 4 h under salt stress. qRT-P-CR and transcription analysis showed that the expression of CaHDZ03 and CaHDZ10 was upregulated under short-term salt stress, but CaHDZ10 was downregulated with long-term salt stress, which provided a theoretical basis for research the function of Ca-HDZIP in response to abiotic stress.